2017
DOI: 10.1093/comnet/cnx047
|View full text |Cite
|
Sign up to set email alerts
|

Labelled network subgraphs reveal stylistic subtleties in written texts

Abstract: The vast amount of data and increase of computational capacity have allowed the analysis of texts from several perspectives, including the representation of texts as complex networks. Nodes of the network represent the words, and edges represent some relationship, usually word co-occurrence. Even though networked representations have been applied to study some tasks, such approaches are not usually combined with traditional models relying upon statistical paradigms. Because networked models are able to grasp t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 52 publications
(74 reference statements)
0
6
0
Order By: Relevance
“…A different approach to analyze co-occurrence networks was devised in [36]. Whilst most approaches only considered traditional network measurements or devised novel topological and dynamical measurements, the authors combined networked and semantic information to improve the performance of network-based classification.…”
Section: Related Workmentioning
confidence: 99%
“…A different approach to analyze co-occurrence networks was devised in [36]. Whilst most approaches only considered traditional network measurements or devised novel topological and dynamical measurements, the authors combined networked and semantic information to improve the performance of network-based classification.…”
Section: Related Workmentioning
confidence: 99%
“…More recently, an approach based on labelled motifs showed that authors tend to use words in combination with particular motifs [49].…”
Section: Motifsmentioning
confidence: 99%
“…A similar idea could also be applied to the analysis of other stylometric tasks. In addition, we suggest that the semantics of the texts could be combined with the concept of semantic flow by using ''labeled motifs'', as proposed in our previous work [59]. Since semantic networks have been studied in cognitive sciences, we believe that the adopted network representation could be adapted and used -as an auxiliary tool -to study complex brain and cognitive processes that could assist the diagnosis of cognitive disorders via text analysis [73,75].…”
Section: Resultsmentioning
confidence: 99%
“…For example, in the authorship recognition task, patterns extracted from a semantic flow analysis could be combined with other techniques to improve the characterization of authors [73,74]. In fact, the use of motifs in the microscopic level has already provided a good characterization of authors [59]. A similar idea could also be applied to the analysis of other stylometric tasks.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation